Ecological drivers of evolution of swine influenza in the United States: a review - Varun Goel; Jessica Ding; Bijaya Hatuwal; Emily Giri; Thomas J. Deliberto; James Lowe; Richard Webby; Michael Emch; Xiu-Feng Wan (Emerging Microbes and Infections)
Influenza A viruses (IAVs) pose a major public health threat due to their wide host range and pandemic potential. Pigs have been proposed as “mixing vessels” for avian, swine, and human IAVs, significantly contributing to influenza ecology. In the United States, IAVs are enzootic in commercial swine farming operations, with numerous genetic and antigenic IAV variants having emerged in the past two decades. However, the dynamics of intensive swine farming systems and their interactions with ecological factors influencing IAV evolution have not been systematically analysed. This review examines the evolution of swine IAVs in commercial farms, highlighting the role of multilevel ecological factors. A total of 61 articles published after 2000 were reviewed, with most studies conducted after 2009 in Midwestern US, followed by Southeast and South-central US. The findings reveal that ecological factors at multiple spatial scales, such as regional transportation networks, interconnectedness of swine operations, farm environments, and presence of high-density, low-genetic diversity herds, can facilitate virus transmission and enhance virus evolution. Additionally, interactions at various interfaces, such as between commercial swine and feral swine, humans, or wild birds contribute to the increase in genetic diversity of swine IAVs. The review underscores the need for comprehensive studies and improved data collection to better understand the ecological dynamics influencing swine IAV evolution. This understanding is crucial for mitigating disease burden in swine production and reducing the risk of zoonotic influenza outbreaks.